The star outside my window - Raúf, Onjali Q. 1981- (Delacorte Press, 2021)
Ten-year-old Aniyah and her little brother Noah find themselves living in foster care after the sudden disappearance of their mom, but with her life in disarray, Aniyah knows just one thing for sure--her mom is not gone forever
Originally published in paperback by Orion Children's Books, an imprint of Hachette Children's Group of Hodder and Stoughton, Hachette UK, London, in 2019
Keywords: Geschwister; Häusliche Gewalt; Foster children / Juvenile fiction; Foster home care / Juvenile fiction; Brothers and sisters / Juvenile fiction; Family violence / Juvenile fiction; Foster children / Fiction; Foster home care / Fiction; Frères et surs / Romans, nouvelles, etc. pour la jeunesse; Violence familiale / Romans, nouvelles, etc. pour la jeunesse; Siblings / Juvenile fiction; Domestic violence / Juvenile fiction; Parents / Family / Juvenile fiction; Orphans & Foster Homes / Family / Juvenile fiction; Physical & Emotional Abuse / Social themes / Juvenile fiction; Kinderbuch